PRELIMINARY ASSESSMENT OF PLANT DIVERSITY IN FOUR HABITAT TYPES IN REBONJARO SURVEY AREA, SOUTH SUMATRA - Guntur Pragustiandi; Ina Aprillia; Melto Sevli (Universitas Medan Area, 2026)
Land-use change in tropical landscapes poses increasing threats to plant diversity, yet baseline floristic data from transitional forest–agroecosystem areas in South Sumatra remain limited. This study aimed to document plant species diversity, floristic composition, and conservation status across four habitat types in the Rebonjaro forest landscape: secondary forest, shrubland, mixed rubber plantation, and oil palm plantation. Vegetation surveys were conducted in 2024 using purposive belt line transects adapted from rapid vegetation assessment methods. Species were recorded through direct field observation within ±10 m of transect lines, with transect lengths ranging from 100–300 m. Conservation status was assessed using the IUCN Red List (version 2024-2) and Indonesia’s Ministry of Environment and Forestry Regulation No. 106/2018. A total of 175 plant species representing 61 families were recorded, with Euphorbiaceae, Fabaceae, and Moraceae being the most species-rich families. Most species were categorized as Least Concern, while Aquilaria malaccensis was identified as Critically Endangered and Gluta renghas and Syzygium laxiflorum as Near Threatened. The results indicate that modified landscapes, particularly mixed rubber plantations, retain considerable plant diversity. This checklist provides essential baseline data to support long-term biodiversity monitoring and conservation planning in landscapes undergoing rapid land-use change.